Faktor Rasio Keuangan terhadap Sustainability Perbankan di Indonesia: Menggunakan Regresi Logistik - Titis Miranti (Jurnal Ekonomi Akuntansi dan Manajemen, 2018)
This study aims to look at the variables that affect financial sustainability. The data used are banking financial statement data contained in the FSS in 2013 to 2017. The value used to measure financial sustainability is FSS. The value of FSS as the dependent variable is divided into two categories, namely banks that are sustainable and banks that are not sustainable. Response variables used are financial ratios consisting of ROA, ROE, CTD, LTD, DTA, and CTA. The analysis used is logistic regression. Based on the results of the logistic regression model that is formed, a significant variable influences sustainability is ROA and LTA. The odds ratio values ​​for the ROA and ROE variables are 1.2 and 2.2. This means that there is an increasing trend of 1.2 and 2.2 times for better financial sustainability with each added value of ROA and ROE. In other words, the greater the value of ROA or ROE, the greater the possibility of banking for financial sustainability. Chi-square test shows the p-value of 0.27 is greater than alpha. This shows the model meets the goodness of fit. Keywords: Financial Sustainability, Financial Ratio, Logistic Regression, Odds Ratio